If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ab + -3a + -2b = 6 Reorder the terms: -3a + ab + -2b = 6 Solving -3a + ab + -2b = 6 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2b' to each side of the equation. -3a + ab + -2b + 2b = 6 + 2b Combine like terms: -2b + 2b = 0 -3a + ab + 0 = 6 + 2b -3a + ab = 6 + 2b Reorder the terms: -6 + -3a + ab + -2b = 6 + 2b + -6 + -2b Reorder the terms: -6 + -3a + ab + -2b = 6 + -6 + 2b + -2b Combine like terms: 6 + -6 = 0 -6 + -3a + ab + -2b = 0 + 2b + -2b -6 + -3a + ab + -2b = 2b + -2b Combine like terms: 2b + -2b = 0 -6 + -3a + ab + -2b = 0 The solution to this equation could not be determined.
| 3(4+(-2y))+4y=2 | | 2(5x-9)=12 | | -14x+7y=-9 | | 2(5x+7)=74 | | -14x+u=-9 | | 3x+5yi=15-7i | | -(n+8)+n=-6n+2(3n-4) | | 2(2x+1)=52 | | 12(3n-7)+8=-2(4-3n) | | 12+7x=4(4x+1)-1 | | 7x-1-2x=5x | | 1m+2m+3m=-15 | | 85=ln(y) | | 2x^2-8x+4m-2=0 | | 0.8x+0.12=2x-2.4 | | 3x+12=2(x-4) | | 2x-23=x+5 | | 1m+2m+9m=33 | | 2n+4n+3n=33 | | 3(x-9)=0 | | 1n+2n+3n=33 | | 3(3x+2)=69 | | 2.8x=2.52 | | .1(6)+x=.2(6+x) | | 5(2x-5)=55 | | 3x-6=(-21) | | X^2-8q+7=0 | | 3x-8y=5fory | | 80x^4+76x^3-24x^2= | | 5v*11-2b=50 | | -2(3x-2)=4 | | 9x+7x-6x=33+7 |